Clinical nursing skills & techniques - Perry, Anne Griffin; Potter, Patricia Ann; Ostendorf, Wendy (St. Louis, Missouri : Elsevier, 2018)
Clinical Nursing Skills & Techniques offers clear and comprehensive coverage of over 200 basic, intermediate and advanced skills. Features nearly 1,000 full-color photographs and drawings, a nursing process framework, step-by-step instructions with rationales, and a focus on critical thinking and evidence-based practice. This edition also includes new coverage of patient-centered care and safety guidelines, an enhanced emphasis on QSEN core competencies, and an expanded clinical focus with specialized Clinical Debriefs, Teach-Back, and sample documentation throughout.
Supporting the patient through the health care system -- Vital signs and physical assessment -- Special procedures -- Infection control -- Activity and mobility -- Safety and comfort -- Hygiene -- Medications -- Oxygenation -- Fluid balance -- Nutrition -- Elimination -- Care of the surgical patient -- Dressings and wound care -- Home care -- Appendixes.
Includes bibliographical references and index.
Keywords: Nursing -- Handbooks, manuals, etc; Nursing Care -- methods; Clinical Medicine -- methods; Evidence-Based Nursing -- methods; Nursing; Handbooks; Handbooks and manuals